2016
DOI: 10.1266/ggs.15-00058
|View full text |Cite
|
Sign up to set email alerts
|

Development of primer sets that can verify the enrichment of histone modifications, and their application to examining vernalization-mediated chromatin changes in <i>Brassica rapa</i> L.

Abstract: Epigenetic regulation is crucial for the development of plants and for adaptation to a changing environment. Recently, genome-wide profiles of histone modifications have been determined by a combination of chromatin immunoprecipitation (ChIP) and genomic tiling arrays (ChIP on chip) or ChIP and high-throughput sequencing (ChIP-seq) in species including Arabidopsis thaliana, rice and maize. Validation of ChIP analysis by PCR or qPCR using positive and negative regions of histone modification is necessary. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 49 publications
(59 reference statements)
1
33
0
Order By: Relevance
“…Characterization of histone modifications has also been initiated in other Brassica species (e.g., Chinese cabbage, Kawanabe et al, 2016). To the best of our knowledge, however, ChIP experiments have not hitherto been performed on field samples through different seasons, and nothing is known about how histone modifications may change in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of histone modifications has also been initiated in other Brassica species (e.g., Chinese cabbage, Kawanabe et al, 2016). To the best of our knowledge, however, ChIP experiments have not hitherto been performed on field samples through different seasons, and nothing is known about how histone modifications may change in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Before cold treatment, only BrFLC1 showed accumulation of both H3K4me3 and H3K36me3 modifications, while three of the BrFLC paralogs (BrFLC2, BrFLC3, and BrFLC5) had only H3K4me3. After 4 weeks of cold treatment, the accumulation of H3K27me3 was observed in BrFLC1, BrFLC2, and BrFLC3, and H3K27me3 was maintained after returning to a warm temperature [85]. These results indicate that, like A. thaliana, the repression of BrFLC expression by prolonged cold treatment was associated with the states of histone modification.…”
Section: Regulation Of Flcs By Vernalization In the Genus Brassicamentioning
confidence: 73%
“…In B. rapa, it has been shown that there is a difference in the expression levels of the FLC paralogs [85]. The coding sequences for the FLC paralogs are relatively conserved between Brassica species, but the alignment of the upstream sequences or introns are more divergent [57].…”
Section: Regulation Of Flcs By Vernalization In the Genus Brassicamentioning
confidence: 99%
“…In Chinese cabbage, the reduced transcription of FLC could be an important factor in premature bolting (Itabashi et al, 2018;Shea et al, 2018;Su et al, 2018;Takada et al, 2019). There are four FLC paralogs in B. rapa and at least three of them act as floral repressors (Kawanabe et al, 2016;Kim et al, 2007;Schranz et al, 2002;Takada et al, 2019). All FLC paralogs were downregulated by prolonged cold treatment, and an increased level of H3K27me3 was observed around the first exon in all FLC paralogs in Chinese cabbage (Akter et al, 2019;Kawanabe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are four FLC paralogs in B. rapa and at least three of them act as floral repressors (Kawanabe et al, 2016;Kim et al, 2007;Schranz et al, 2002;Takada et al, 2019). All FLC paralogs were downregulated by prolonged cold treatment, and an increased level of H3K27me3 was observed around the first exon in all FLC paralogs in Chinese cabbage (Akter et al, 2019;Kawanabe et al, 2016). Following a return to normal temperature growth conditions, H3K27me3 spreads along all four BrFLC paralogs providing stable repression of the gene (Akter et al, 2019;Takada et al, 2019).…”
Section: Introductionmentioning
confidence: 99%